Functional, RF‐Trilayer Sensors for Tooth‐Mounted, Wireless Monitoring of the Oral Cavity and Food Consumption. Issue 18 (23rd March 2018) - Tseng, Peter; Napier, Bradley; Garbarini, Logan; Kaplan, David L.; Omenetto, Fiorenzo G.
Abstract: Wearable devices have emerged as powerful tools for personalized healthcare in spite of some challenges that limit their widespread applicability as continuous monitors of physiological information. Here, a materials‐based strategy to add utility to traditional dielectric sensors by developing a conformal radiofrequency (RF) construct composed of an active layer encapsulated between two reverse‐facing split ring resonators is applied. These small (down to 2 mm × 2 mm) passive dielectric sensors possess enhanced sensitivity and can be further augmented by functionalization of this interlayer material. Demonstrator devices are shown where the interlayer is: (i) a porous silk film, and (ii) a modified PNIPAM hydrogel that swells with pH or temperature. In vivo use is demonstrated by adhesion of the device on tooth enamel to detect foods during human ingestion. Such sensors can be easily multiplexed and yield data‐rich temporal information during the diffusion of analytes within the trilayer structure. This format could be extended to a suite of interlayer materials for sensing devices of added use and specificity. Abstract : A small‐form‐factor, biopolymer‐based layered radiofrequency sensor is developed for sensing various solutes, pH, and temperature. An interchangeable sensitive layer determines the response to either analyte‐induced dielectric change, or pH‐ and temperature‐induced mechanical change. On‐tooth sensing is demonstrated for tracking of food intake.